The Doctor-Patient Relationship in the Changing Health Scene. - Gallagher, Eugene B. (Bethesda : U.S. Department of Health, Education, and Welfare, 1978)
GALLAGHER (E. B.), Conference Background and Objectives
LEAVITT, Jr. (M. D.), Welcome to the Conference
GODBER (Sir G.), Introduction
BLOOM (S. W.) and SUMMEY (P.), Models of the Doctor-Patient Relationship : A history of the Social System Concept
PFLANZ (M.), The Two Faces of the Patient-Doctor Relationship in a Changing Welfare State : Federal Republic of Germany
HERZLICH (C.), Conceptions of the Doctor-Patient Relationship in the French Medical Press
STIMSON (G. V.), Interaction between Patients and General Practitioners in the United Kingdom
SCHEFF (T. J.), Emotion Work and Distancing in Medical Settings
LAZARE (A.) et al., Studies on a Negociated Approach to Patienthood
GILL (D. G.), Limitations upon Choice and Constraints over Decisionmaking in Doctor-Patient Exchanges
McKINLAY (J. B.), The Changing Political and Economic Context of the Patient-Physician Encounter
PRATT (L. V.), Reshaping the Consumer's Posture in Health Care
KELMAN (H. R.), Consumer Criteria of Health Services Quality
BIRCH (J. S.) and. WOLFE (S.), Recently Pregnant Women Evaluate Alternative Health Care Services
HAUG (M. R.), Issues of Patient Acceptance of Physician Authority in Great Britain
LACRONIQUE (J.-F.), Technology and Medicine in Contemporary France
GALLAGHER (E. B.), Patients, Doctors, and Policies in Renal Dialysis : Cross-national trends
WAITZKIN (H. B.), How Capitalism Cares for our Coronaries : A preliminary Exercise in Political Economy
RABIN (D. L.), Variations in Physician Encounters : An international perspective
HOWARD (J.), Patient-Centric Technologies : A case for "soft science"
PENE (P. J.), Medical Care and the Family Doctor in Marseilles, France
HAYNES (M. A.), Medical Care and the Doctor-Patient Relationship
COLE (J. W.), Family Practitioners, Specialists, and Allied Health Practitioners : A new dimension in the doctor-patient relationship
BOWERS (J. Z.), Migration, Manpower, and the Doctor-Patient Relationship
STRAUS (R.), Medical Education and the Doctor-Patient Relationship
Proc. Intern. Conf. held at the National Institutes of Health (Bethesda, April 26-28, 1976)
Bibliogr. dissém., index.
0023